2019
DOI: 10.1016/j.bja.2018.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Non-opioid analgesic modes of pain management are associated with reduced postoperative complications and resource utilisation: a retrospective study of obstructive sleep apnoea patients undergoing elective joint arthroplasty

Abstract: Background: Studies on the effectiveness of multimodal analgesia, particularly in patients at higher perioperative risk from obstructive sleep apnoea (OSA), are lacking. We aimed to assess the impact of multimodal analgesia on opioid use and complications in this high-risk cohort. Methods: We conducted a population-based retrospective cohort study of OSA patients undergoing elective lower extremity joint arthroplasty (2006e16, Premier Healthcare database). Multimodal analgesia was defined as opioid use with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 46 publications
1
23
0
1
Order By: Relevance
“…Recent clinical study documented that co administration of opioid and GBP provided reduction in opioid use and complications this study also noticed the clinical benefit including critical respiratory failure [66]. Recently, increasing number of clinical reports on efficacy of gabapentin (pre and post-operative) on 'morphine consumption' and in 'reducing pain intensity' have been documented [64][65][66][67][68]. Thus the present study strongly indicated to reveal the functional molecular singling circuits of 'combination of morphine and gabapentin' observed in clinical reports.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Recent clinical study documented that co administration of opioid and GBP provided reduction in opioid use and complications this study also noticed the clinical benefit including critical respiratory failure [66]. Recently, increasing number of clinical reports on efficacy of gabapentin (pre and post-operative) on 'morphine consumption' and in 'reducing pain intensity' have been documented [64][65][66][67][68]. Thus the present study strongly indicated to reveal the functional molecular singling circuits of 'combination of morphine and gabapentin' observed in clinical reports.…”
Section: Discussionmentioning
confidence: 66%
“…Evidences based on clinical studies showed that the combination of morphine and gabapentin yielded better analgesia than morphine alone with safety [64,65]. Recent clinical study documented that co administration of opioid and GBP provided reduction in opioid use and complications this study also noticed the clinical benefit including critical respiratory failure [66]. Recently, increasing number of clinical reports on efficacy of gabapentin (pre and post-operative) on 'morphine consumption' and in 'reducing pain intensity' have been documented [64][65][66][67][68].…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, we found evidence for an association between opioid prescription levels and complication risk in the past 4. While in the current study we did not compare the risk of pulmonary and other complications between patients with and without benzodiazepine or opioid utilization as part of regional anesthesia, we identified the use of multimodal analgesia reducing opioid use in the OSA population to be indeed beneficial and able to reduce a number of complications 5. We concur, however, that future research regarding this topic would provide further interesting information.…”
mentioning
confidence: 51%
“…Though our findings were unexpected, further review of the published literature reveals a growing body of evidence that low-dose intraoperative ketamine may be ineffective in other populations as well. Cozowicz et al published a retrospective study of 181,182 patients looking specifically at the use of multimodal analgesia in OSA patients who underwent elective joint arthroplasty [14]. In their multivariate analysis, COX-2 inhibitors and NSAIDs (non-steroidal anti-inflammatory drugs) were very effective in reducing post-operative opioid utilization; however, ketamine had no significant impact on opioid utilization.…”
Section: Discussionmentioning
confidence: 99%